Economia comportamental e régua de cobrança para recuperação de créditos tributários na Cidade de Fortaleza - Barbosa Júnior, Ney Lopes (2020)
This paper presents a management model for administrative recovery of delinquent tax credits, before the application for registration in active debt, whose collection from 2014, by law, was in charge of the Attorney General's Office of Active Debt of the Municipality of Fortaleza. The criteria to maximize the recovery of those credits will be detailed, respecting the constitutional restrictions inherent to the power to tax, with the lowest possible operational cost, always with regard to the legal institute of the prescription for the effective control and reduction of delinquency in the municipality. For these objectives to be achieved it is necessary to define the strategy of administrative collection actions most appropriate to the culture and resources existing in the collection body, the form and means of communication to be employed between the tax man and the taxpayer, with the use of Behavioral Economics techniques, in addition to the foundations for the implementation of a Collection Rule , which identifies the ideal profile of the debtor of each type of tribute. The process requires the development of Business Intelligence (BI) tools that enable, at any time, the analysis of the implemented experiments, the monitoring of ongoing or finalized actions, the measurement of the operational cost for receiving the tax credit due in relation to those practiced by the market and other collecting agents, in order to optimize, within the deadlines and legal limits , the administrative recovery of the credit due, which reinforces and consolidates before the taxpayer the tax presence and zeal of the Tax Administration of Fortaleza with the Municipal Public Revenue. The experiment showed obtained results that were improving over time, presenting individual results of lots in the order of 80.64% referring to the amount of DAMs paid in the total and 61% referring to the amount paid of the total with a cost of 1.38% (ratio of value spent per amount received) representing around one third of that practiced by the market.